Method for producing polyvinyl alcohol resin
Patent Information
- Application Number
- JP2022512231
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2021-03-29
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-03-29
AI Technical Summary
【0008】 本発明は、上記のとおり、280nmにおける吸光度が0.2以上であるポリビニルアルコール系樹脂の製造方法であって、原料のポリビニルアルコール系樹脂を溶融混練し、シート状に押し出す工程、シート状のポリビニルアルコール系樹脂を冷却する工程、冷却したシート状のポリビニルアルコール系樹脂を粉砕する工程を備える。したがって、従来のようにポリビニルアルコール系樹脂をストランド状ではなく、シート状に押し出すため、押出機の吐出量を上げることができ、生産性を高めることができる。また、ストランド状とは異なりシート状に押し出すことで、吐出量を上げても吐出部付近で樹脂の滞留が起こりにくく、優れたロングラン性を有する。さらには、表面積の広いシート状にすることで、非常に効率的にポリビニルアルコール系樹脂を粉砕可能な温度まで冷却できるため、押出機の吐出量を上げ、ポリビニルアルコール系樹脂が高い熱量を持っている場合でも効率的に冷却粉砕が可能となる。つまり、高生産性で粉砕処理されたポリビニルアルコール系樹脂を得ることができるのである。本発明の製造方法で得られたポリビニルアルコール系樹脂は、ビニル系化合物、特には塩化ビニルの懸濁重合用分散剤として有用である。
Smart Images

Figure 0007635780000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a polyvinyl alcohol-based resin, and more specifically, to a method for producing a polyvinyl alcohol-based resin having high productivity and excellent long-run properties. [Background technology]
[0002] Conventionally, polyvinyl alcohol resins having conjugated double bonds in the molecule have been used as dispersants in the suspension polymerization of vinyl compounds such as vinyl chloride. The polyvinyl alcohol resins having conjugated double bonds in the molecule are usually obtained by heat treating a polyvinyl alcohol resin or a carbonyl group-containing polyvinyl alcohol resin, thereby removing fatty acids (e.g., deacetylation) to generate double bonds. For example, Patent Document 1 discloses that a polyvinyl alcohol resin having a conjugated double bond in the molecule can be obtained by melt-kneading the carbonyl group-containing polyvinyl alcohol resin in an extruder, heat-treating the resin, and then extruding the resin into a strand shape and pulverizing the strand. The amount of the conjugated double bond can be determined using absorbance as an index. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2004-250695 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the production method of polyvinyl alcohol resin disclosed in the above Patent Document 1 does not have a very high productivity, and further improvement is required to increase the productivity. That is, polyvinyl alcohol resin is water-soluble, and the polyvinyl alcohol resin extruded in a strand shape from the extruder cannot be cooled by water cooling, so it must be cooled by air cooling, making it difficult to increase productivity. In addition, if the discharge rate of the extruder is increased to increase productivity, the amount of polyvinyl alcohol resin increases and the amount of heat retained also increases, so that normal air cooling is insufficient to cool the extruded strands, sheets, etc., making it difficult to cut or crush them. In addition, gel is easily generated near the discharge section, and long-run properties are reduced.
[0005] Therefore, the present invention provides a method for producing a polyvinyl alcohol-based resin having high productivity and excellent long-run properties. [Means for solving the problem]
[0006] Means for Solving the Problems The present inventors conducted intensive research in light of the above circumstances and found that the above problems can be solved by extruding the polyvinyl alcohol-based resin after melt kneading into a sheet shape rather than a strand shape, and cooling the sheet-shaped polyvinyl alcohol-based resin.
[0007] That is, the gist of the present invention is the following [1] to [4]. [1] A method for producing a polyvinyl alcohol-based resin having an absorbance of 0.2 or more at 280 nm, comprising the steps of melt-kneading a raw material polyvinyl alcohol-based resin and extruding it into a sheet, cooling the sheet-like polyvinyl alcohol-based resin, and pulverizing the cooled sheet-like polyvinyl alcohol-based resin. [2] The method for producing a polyvinyl alcohol-based resin according to [1], wherein the raw material polyvinyl alcohol-based resin is a carbonyl group-containing polyvinyl alcohol-based resin. [3] The method for producing a polyvinyl alcohol-based resin according to [1] or [2], wherein the step of cooling the sheet-like polyvinyl alcohol-based resin is a step of cooling the sheet-like polyvinyl alcohol-based resin by sandwiching it between a belt cooler. [4] The method for producing a polyvinyl alcohol-based resin according to any one of [1] to [3], for producing a polyvinyl alcohol-based resin used as a dispersant for suspension polymerization of a vinyl compound. Effect of the Invention
[0008] As described above, the present invention is a method for producing a polyvinyl alcohol resin having an absorbance of 0.2 or more at 280 nm, comprising the steps of melt-kneading a raw material polyvinyl alcohol resin and extruding it into a sheet, cooling the sheet-shaped polyvinyl alcohol resin, and pulverizing the cooled sheet-shaped polyvinyl alcohol resin. Therefore, since the polyvinyl alcohol resin is extruded into a sheet shape rather than into a strand shape as in the past, the discharge rate of the extruder can be increased, and productivity can be improved. In addition, by extruding into a sheet shape, unlike a strand shape, the resin is less likely to remain near the discharge section even if the discharge rate is increased, and the method has excellent long-run properties. Furthermore, by extruding into a sheet shape with a large surface area, the polyvinyl alcohol resin can be cooled very efficiently to a temperature at which it can be pulverized, and the discharge rate of the extruder can be increased, and even if the polyvinyl alcohol resin has a high heat value, the polyvinyl alcohol resin can be efficiently cooled and pulverized. In other words, a polyvinyl alcohol resin pulverized with high productivity can be obtained. The polyvinyl alcohol resin obtained by the production method of the present invention is useful as a dispersant for suspension polymerization of vinyl compounds, particularly vinyl chloride. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The configuration of the present invention will be described in detail below, but these are merely examples of preferred embodiments.
[0010] The polyvinyl alcohol (hereinafter referred to as "PVA") resin obtained by the production method of the present invention is mainly used as a dispersant for suspension polymerization of vinyl compounds, and is obtained by introducing a conjugated double bond into the raw material PVA resin. First, prior to the production method of the present invention, the raw material PVA resin used in the production method of the present invention will be described.
[0011] [PVA resin raw material] The PVA-based resin used as the raw material in the production method of the present invention is not particularly limited, but a PVA-based resin having a carbonyl group in the molecule is preferred because it allows efficient introduction of conjugated double bonds into the molecule.
[0012] The method for producing the PVA resin having a carbonyl group is not particularly limited, and may be any known method, for example, (1) A method in which a PVA resin obtained by saponifying a polyvinyl ester resin obtained by polymerizing a vinyl ester compound is oxidized with an oxidizing agent such as hydrogen peroxide; (2) A method in which a vinyl ester compound is polymerized in the presence of a chain transfer agent containing a carbonyl group, such as an aldehyde or a ketone, and then saponification is carried out. (3) A method in which a vinyl ester compound is polymerized in the presence of 1-methoxyvinyl acetate or the like to produce a polyvinyl ester resin, and the polyvinyl ester resin is then saponified. (4) A method in which air is blown into the system during polymerization of a vinyl ester compound to obtain a polyvinyl ester resin, and then saponification is carried out. etc. Among them, the above method (2) is preferred from the viewpoint of productivity. The method (2), which is a preferred method for producing a carbonyl group-containing PVA resin, will be described in detail below.
[0013] Examples of the vinyl ester-based compound used in the polymerization include vinyl formate, vinyl acetate, vinyl trifluoroacetate, vinyl propionate, vinyl butyrate, vinyl caprate, vinyl laurate, vinyl versatate, vinyl palmitate, and vinyl stearate. Of these, it is preferable to use vinyl acetate. The vinyl ester-based compounds may be used alone or in combination of two or more kinds.
[0014] In addition, as a polymerization component other than the vinyl ester compound, other monomers polymerizable with the vinyl ester compound can be used in an amount of 15 mol % or less, preferably 5 mol % or less, of the polymerization components.
[0015] Examples of the other monomers include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, and monoalkyl maleates, or alkyl esters of these unsaturated acids, nitriles or amides such as acrylonitrile, methacrylonitrile, acrylamide, and methacrylamide, olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid, or salts thereof, vinyl esters other than fatty acid vinyl, vinyl ethers, vinyl ketones, ethylene, α-olefins, vinyl halides, vinylidene halides, vinyl ethylene carbonate, and 3,4-diacetoxy-1-butene. These may be used alone or in combination of two or more.
[0016] Examples of the chain transfer agent containing a carbonyl group, such as the aldehydes and ketones (hereinafter simply referred to as "chain transfer agent"), include aldehydes such as acetaldehyde, propionaldehyde, n-butylaldehyde, benzaldehyde, and crotonaldehyde, and ketones such as acetone, methyl ethyl ketone, hexanone, and cyclohexanone. Among these, acetaldehyde, benzaldehyde, propionaldehyde, and n-butylaldehyde are preferred because of the ease of controlling the chain transfer of the vinyl ester compound to the carbonyl compound. The chain transfer agent may be used alone or in combination of two or more kinds.
[0017] The amount of the chain transfer agent is adjusted depending on the chain transfer constant of the chain transfer agent to be added and the polymerization degree of the target PVA resin, and is usually preferably 0.1 to 5% by weight, more preferably 0.5 to 3% by weight, based on the polymerization components. The chain transfer agent may be charged all at once at the beginning of polymerization, or may be charged during polymerization. By charging the chain transfer agent by any method, the molecular weight distribution of the PVA resin can be controlled.
[0018] The polymerization method for the vinyl ester compound is not particularly limited, and examples thereof include known polymerization methods such as solution polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization, among which solution polymerization is preferred.
[0019] As a solvent used in the above solution polymerization, an alcohol such as methanol, ethanol, isopropyl alcohol, etc. is usually used. In the above solution polymerization, the polymerization components may be charged in portions or all at once, or may be added continuously or intermittently, or any other means may be used.
[0020] As the polymerization initiator for the solution polymerization, for example, azobisisobutyronitrile, acetyl peroxide, benzoyl peroxide, lauroyl peroxide, azobisdimethylvaleronitrile, azobismethoxyvaleronitrile, etc., known radical polymerization initiators can be used. The polymerization reaction temperature is selected from the range of 40°C to the boiling point of the solvent.
[0021] The saponification of the polyvinyl ester resin obtained above can be carried out by a known method, and is usually carried out in the presence of an alkali catalyst or an acid catalyst after dissolving the polyvinyl ester resin in alcohol. As the alcohol, for example, methanol, ethanol, butanol, isopropanol, or a mixed solvent of various alcohols and methyl acetate, such as a mixed solvent of methanol and methyl acetate, can be used. The concentration of the polyvinyl ester resin in the alcohol is selected from the range of 20 to 50% by weight.
[0022] In addition, the saponification is preferably carried out in a solvent having a dielectric constant of 32 or less from the viewpoint of controlling the block character described later. Examples of solvents having a dielectric constant of 32 or less include methanol (31.2), methyl acetate / methanol = 1 / 3 [weight ratio] (27.1), methyl acetate / methanol = 1 / 1 [weight ratio] (21.0), methyl acetate / methanol = 3 / 1 [weight ratio] (13.9), methyl acetate (7.03), isopropyl acetate (6.3), trichloroethylene (3.42), xylene (2.37), toluene (2.38), benzene (2.28), and acetone (21.4). Among these, metamel is preferably used. The numbers in parentheses above indicate the dielectric constant of each solvent.
[0023] As the alkali catalyst, for example, hydroxides and alcoholates of alkali metals such as sodium hydroxide, potassium hydroxide, sodium methylate, sodium ethylate, potassium methylate, etc. can be used. As the acid catalyst, for example, an aqueous solution of an inorganic acid such as hydrochloric acid or sulfuric acid, or an organic acid such as p-toluenesulfonic acid can be used. The amount of the alkali catalyst or acid catalyst used is preferably 1 to 100 millimolar equivalents, more preferably 1 to 40 millimolar equivalents, and even more preferably 1 to 20 millimolar equivalents, per mole of the vinyl ester compound. If the amount of the alkali catalyst or acid catalyst used is too small, it tends to be difficult to increase the saponification degree to the desired level, while if the amount of the alkali catalyst or acid catalyst used is too large, the saponification degree tends to be higher than the desired level.
[0024] The temperature at which the saponification is carried out is not particularly limited, but is preferably from 10 to 70°C, more preferably from 20 to 50°C.
[0025] The saponification method includes continuous saponification on a belt dweller and batch saponification. In the case of continuous saponification, the saponification reaction is usually about 15 to 20 minutes, and in the case of batch saponification, the saponification reaction is usually 2 to 3 hours.
[0026] The saponification degree of the carbonyl group-containing PVA resin obtained as described above is preferably 65 to 98 mol%, more preferably 68 to 85 mol%, and even more preferably 68 to 82 mol%. If the saponification degree is too low, the water dispersibility tends to deteriorate, and if the saponification degree is too high, when used as a dispersant, the surface activity decreases, the dispersibility of vinyl compounds deteriorates, and blocks tend to be easily formed during suspension polymerization.
[0027] The average degree of polymerization of the carbonyl group-containing PVA resin is preferably 200 to 3000, more preferably 400 to 1200. If the average degree of polymerization is too low, when used in suspension polymerization of a vinyl compound, the protective colloid properties become too low and aggregation tends to occur during suspension polymerization, whereas if the average degree of polymerization is too high, the plasticizer absorption of the polyvinyl resin obtained by suspension polymerization tends to decrease.
[0028] The carbonyl group content in the carbonyl group-containing PVA resin is preferably 0.05 mol% or more, more preferably 0.1 mol% or more, and preferably 0.5 mol% or less. If the content is too small, the introduction of conjugated double bonds during melt-kneading described below becomes insufficient, the protective colloid properties as a dispersant decrease, and the amount of dispersant used tends to increase.
[0029] In addition, since a part of the 1,2-glycol bonds contained in the carbonyl group-containing PVA resin is broken and a carbonyl group is further introduced during melt kneading as described below, the 1,2-glycol bond content in the carbonyl group-containing PVA resin is preferably 1.0 to 3.5 mol%. Here, "a part of the 1,2-glycol bonds" means within 15% of the total amount of 1,2-glycol bonds contained in the carbonyl group-containing PVA resin. The amount of 1,2-glycol bonds can be controlled by the temperature during polymerization.
[0030] Furthermore, the carbonyl group-containing PVA resin preferably contains a salt or hydroxide of a monovalent to trivalent metal, since this promotes the elimination of fatty acids such as acetic acid from the residual fatty acid group adjacent to the carbonyl group in the molecule during melt kneading as described below.
[0031] Examples of the monovalent to trivalent metal include alkali metals such as sodium, magnesium, calcium, and zinc, alkaline earth metals, and aluminum, etc. Among these, at least one selected from the group consisting of sodium, magnesium, and calcium is preferred, and calcium and magnesium are particularly preferred, in that fatty acids can be efficiently eliminated from the residual fatty acid group adjacent to the carbonyl group in the molecule.
[0032] The salts of the monovalent to trivalent metals are preferably aliphatic carboxylates having 3 or less carbon atoms, from the viewpoint of ease of industrial handling, such as solubility or swelling in water or alcohols such as methanol. Examples of aliphatic carboxylates having 3 or less carbon atoms include acetates and propionates.
[0033] Specific examples of the salts or hydroxides of the monovalent to trivalent metals include alkali metal salts or alkaline earth metal salts such as aluminum hydroxide, sodium acetate, magnesium acetate, calcium acetate, calcium propionate, and zinc acetate. These may be used alone or in combination of two or more. Among these, magnesium acetate tetrahydrate and calcium acetate are preferred, with magnesium acetate tetrahydrate being particularly preferred, because they can be dissolved in at least one of water and methanol and are easy to handle industrially.
[0034] The content of the salt or hydroxide of the above-mentioned monovalent to trivalent metal is preferably 0.1 to 3 mol%, more preferably 0.2 to 2 mol%, and even more preferably 0.2 to 1.5 mol% based on the carbonyl group-containing PVA-based resin. If the content of the salt or hydroxide of the monovalent to trivalent metal is too small, the production efficiency of conjugated double bonds tends to decrease during melt-kneading. If the content is too large, the carbonyl group-containing PVA-based resin tends to decompose easily during melt-kneading.
[0035] The method of adding the above-mentioned salt or hydroxide of the monovalent to trivalent metal to the carbonyl group-containing PVA-based resin is not particularly limited. For example, it may be directly added to the paste of the polyvinyl ester-based resin before saponification, the slurry after saponification, or the pellets or powder of the carbonyl group-containing PVA-based resin. However, the method of adding it to the slurry after saponification is preferred. When adding to the slurry after saponification, a solution or dispersion having a concentration of 3 to 15% by weight, in which the salt or hydroxide of the monovalent to trivalent metal is dissolved or dispersed in an alcohol such as methanol, ethanol, or propanol or water, may be added to the slurry after saponification.
[0036] In this way, the carbonyl group-containing PVA-based resin used in the production method of the present invention can be prepared. Also, the shape of the carbonyl group-containing PVA-based resin is not particularly limited, but being in powder form is preferred from the viewpoint of workability.
[0037] The above-mentioned carbonyl group-containing PVA-based resin may be used alone, or two or more kinds having different properties may be blended and used. By blending and using two or more kinds, the viscosity, degree of polymerization, degree of saponification, and molecular weight distribution can be adjusted.
[0038] <Method for Producing PVA-Based Resin> Next, a method for producing a polyvinyl alcohol-based resin having an absorbance of 0.2 or more at 280 nm according to the present invention will be described. The production method of the PVA-based resin of the present invention is [1] A step of melt-kneading the raw material PVA-based resin and extruding it into a sheet shape, [2] A step of cooling the sheet-shaped PVA-based resin; [3] A process of crushing the cooled sheet-like PVA-based resin; It is equipped with:
[0039] [1] The process of melting and kneading the raw material PVA resin and extruding it into a sheet. First, the process of melt-kneading the raw material PVA resin and extruding it into a sheet will be described. As the raw material PVA resin, it is preferable to use the above-mentioned carbonyl group-containing PVA resin, and this carbonyl group-containing PVA resin is fed to an extruder and melt-kneaded. This process introduces conjugated double bonds by the fatty acid removal reaction of the fatty acid ester groups remaining in the carbonyl group-containing PVA-based resin. In addition, by using an extruder to melt heat treat the carbonyl group-containing PVA-based resin, the randomness of the distribution of the fatty acid vinyl ester units is improved, and the foaming suppression effect when used as a dispersant is improved.
[0040] The melt-kneading temperature is usually 175 to 250° C., preferably 200 to 240° C. If the melt-kneading temperature is too low, the efficiency of introducing conjugated double bonds tends to decrease, and if the melt-kneading temperature is too high, the carbonyl group-containing PVA resin tends to be easily decomposed, which tends to cause gel formation. In addition, foreign matter such as burnt matter tends to be mixed into the obtained PVA resin.
[0041] The residence time (melt-kneading time) in the extruder is preferably 1 to 15 minutes, more preferably 2 to 10 minutes. If the melt-kneading time is too short, the introduction efficiency of the conjugated double bonds tends to be low, and if the melt-kneading time is too long, foreign matter such as burnt matter tends to be mixed into the obtained PVA-based resin.
[0042] As the extruder, either a single screw extruder or a twin screw extruder can be used, but it is preferable to use a twin screw extruder. As the twin screw extruder, a co-rotating intermeshing twin screw extruder, a counter-rotating intermeshing twin screw extruder, a non-intermeshing twin screw extruder, a switching twin screw extruder, etc. can be used.
[0043] Next, the melt-kneaded PVA resin is extruded into a sheet. Conventionally, the melt-kneaded PVA resin is extruded in the form of a strand, resulting in low productivity. In addition, when the amount of strand discharged is increased to increase productivity, gel is easily generated near the discharge portion, resulting in a decrease in long-run performance. On the other hand, in the manufacturing method of the present invention, the melt-kneaded PVA resin is extruded into a sheet, and the surface area is increased, allowing the molten resin sheet to be efficiently cooled, resulting in high productivity and excellent long-run performance.
[0044] The thickness of the sheet-like PVA resin is usually 1.0 to 5.0 mm, preferably 1.5 to 4.0 mm, and particularly preferably 2.0 to 3.0 mm. If the thickness is too thin, the productivity and long-run property tend to be low, and if the thickness is too thick, it takes a long time to cool, and the productivity tends to be low.
[0045] The width of the sheet-like PVA resin is not particularly limited, and is usually 0.1 to 2.0 m, and preferably 0.15 to 1.0 m.
[0046] [2] Step of cooling the sheet-shaped PVA resin Next, the sheet-like PVA resin obtained above is cooled. Examples of the cooling method for the sheet-shaped PVA resin include a belt cooler, air cooling, and a spot cooler. These may be used alone or in combination of two or more. Among these, a belt cooler is preferred from the viewpoint of cooling efficiency.
[0047] The belt cooler is a device that supplies a sheet-like PVA resin onto a metal belt such as steel (e.g., a stainless steel belt) and sprays water from the bottom of the belt to cool the resin. From the viewpoint of cooling efficiency, a method of cooling the sheet-like PVA resin by sandwiching both sides of the sheet-like PVA resin between belt coolers with cooling control is preferred. That is, by forming the PVA resin into a sheet with a large surface area and sandwiching both the front and back sides of the sheet between belt coolers with cooling control, the PVA resin having a high heat value can be cooled to a temperature at which it can be crushed more efficiently.
[0048] The temperature of the sheet-shaped PVA resin after cooling is usually 40° C. or lower, preferably 30° C. or lower.
[0049] [3] Grinding the cooled sheet-like PVA resin Next, the cooled sheet-like PVA resin is pulverized. The method for pulverizing the sheet-like PVA resin is not particularly limited and can be performed by a known method, but for efficient pulverization, it is preferable to perform pulverization in two stages, that is, it is preferable to perform coarse pulverization of the sheet-like PVA resin and then fine pulverization.
[0050] The apparatus used for coarsely pulverizing and finely pulverizing the PVA-based resin is not particularly limited, and any known apparatus can be used, with an impact type pulverizer being preferred.
[0051] A typical pulverizing method includes, for example, a method in which a PVA-based resin is coarsely pulverized with a hammer crusher, and then the coarsely pulverized PVA-based resin is finely pulverized with a Makino type pulverizer.
[0052] The size of the PVA resin after pulverization is usually 250 to 1500 μm, preferably 350 to 1000 μm, in terms of average particle size.
[0053] The PVA resin produced by the production method of the present invention is useful as a dispersant (primary dispersant) for suspension polymerization of vinyl compounds, particularly vinyl chloride.
[0054] The absorbance of the obtained PVA resin at 280 nm in the ultraviolet absorption spectrum of a 0.1 wt % aqueous solution is 0.2 or more, preferably 0.3 or more, and more preferably 0.4 or more. If the absorbance is too low, when used as a dispersant for suspension polymerization of a vinyl compound, the polymerization stability is low, the particle size distribution of the obtained polymer tends to be broad, and coarse particles tend to be generated. The upper limit of the absorbance is usually 0.7.
[0055] The absorption at 280 nm in the above ultraviolet absorption spectrum is due to -CO-(CH=CH) in the PVA resin. 2 - structure. Therefore, as the amount of conjugated double bonds in PVA resin increases, the absorbance also increases, and when used as a dispersant for suspension polymerization of vinyl compounds, the surface activity such as protective colloid properties is improved.
[0056] In addition, the PVA resin has an absorbance of 320 nm (A 320 ) and absorbance at 280 nm (A 280 ) ratio (A 320 / A 280 ) is preferably 0.3 or more, more preferably 0.45 to 1.5, still more preferably 0.5 to 1.2, particularly preferably 0.6 to 1.2, and particularly preferably 0.8 to 1.2. If the absorbance ratio is too small, the protective colloid properties as a dispersant tend to be low, and the suspension polymerization stability tends to decrease, whereas if the absorbance ratio is too large, foaming of the aqueous PVA resin solution tends to be intense, and scale tends to be generated during suspension polymerization.
[0057] The block character of the fatty acid ester group remaining in the PVA resin is 0.5 or more, and preferably 0.55 or more. If the block character is too low, the foaming suppression effect during suspension polymerization of the vinyl compound tends to decrease.
[0058] The block character indicates the degree of the average chain length of the fatty acid ester units in the PVA-based resin, and the higher the value, the shorter the average chain length of the remaining fatty acid ester blocks (the higher the randomness of the fatty acid ester units).
[0059] The above "block character" (η) is 3-(trimethylsilyl)-2,2,3,3-d 4 -Propionic acid sodium salt (3-(trimethylsilyl)propionic-2,2,3,3-d 4 Use of sodium acidsalt 13 This value is determined from the absorption intensity ratio of the absorption due to the methylene carbon moiety observed in the range of 38 to 49 ppm in C-NMR measurement [absorption of (OH,OH) dyad = 43.5 to 46 ppm, absorption of (OH,OR) dyad = 41.0 to 43.5 ppm, absorption of (OR,OR) dyad = 38 to 40.5], and is calculated from the following formula. [η] = (OH,OR) / 2(OH)(OR) (However, (OH, OR), (OH), and (OR) are all calculated as mole fractions. Also, (OH) is 13 The degree of saponification (molar fraction) is calculated from the integral ratio of C-NMR. For example, when vinyl acetate is used as the fatty acid vinyl, (OR) indicates the molar fraction of acetoxy groups. Block characters and methods for measuring them are described in detail in Poval (published by Polymer Publishing Association, 1984) and Macromolecules, 10, 532 (1977).
[0060] The production method of the present invention has been described above. The PVA-based resin obtained by the production method of the present invention is particularly useful as a dispersant for suspension polymerization of vinyl chloride, but is not limited thereto, and can be suitably used as a dispersant for suspension polymerization of any vinyl-based compound such as styrene, acrylate, methacrylate, vinyl acetate, etc. EXAMPLES
[0061] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0062] (Production of carbonyl group-containing PVA resin) 100 parts of vinyl acetate, 1.2 parts of acetaldehyde, 4.7 parts of methanol, and 0.0092% acetyl peroxide (APO) based on vinyl acetate were charged into a polymerization vessel, and after nitrogen replacement, the vessel was heated to initiate polymerization at boiling point, and polymerization was terminated when the polymerization rate reached 91.8% after about 5.7 hours of reaction time. Next, unpolymerized vinyl acetate was removed, and 7.4 mmol of sodium hydroxide was added to the resulting methanol solution (40% solution) of the polymer, based on 1 mole of polymer vinyl acetate unit, and saponification was carried out at 35°C for 2 hours by a conventional method to prepare a slurry of carbonyl group-containing PVA resin with a resin content of 12% (polymerization degree 770, saponification degree 71.7 mol%, carbonyl group amount 0.16 mol%).
[0063] Next, a 10% methanol solution of magnesium acetate tetrahydrate as a metal compound was added to the carbonyl group-containing PVA resin prepared above at a ratio of 350 g per 1 kg of the carbonyl group-containing PVA resin, and the mixture was stirred for 1 hour at 25° C. After that, the mixture was filtered and dried to obtain a carbonyl group-containing PVA resin containing 1.25 mol % of magnesium acetate.
[0064] <Example 1> The carbonyl group-containing PVA resin obtained above was fed to a twin-screw extruder, melt-kneaded under the manufacturing conditions described below, and extruded into a sheet. Both sides of the sheet-like PVA resin were sandwiched between two belt coolers (manufactured by Nippon Belting Co., Ltd.) for cooling. After that, the resin was pulverized using a hammer crusher (manufactured by Makino Sangyo Co., Ltd.) and a Makino type pulverizer (manufactured by Makino Sangyo Co., Ltd.) to obtain particles of PVA resin with an average particle size of 850 μm.
[0065] [Manufacturing conditions] <Melt kneading conditions> The resin temperature was adjusted to a set temperature using a twin-screw extruder (TEM-58, L / D=45, manufactured by Toshiba Machine Co., Ltd.) and melt kneading was carried out. Temperature settings: C1 / C2 / C3 / C4 / C5 / C6 / C7 / C8 / C9 / C10 / H1 / D1 / D2 / D3 =50 / 200 / 200 / 200 / 220 / 230 / 230 / 240 / 240 / 240 / 240 / 240 / 230 / 240℃ Screw rotation speed: 240 rpm Discharge amount: 250kg / hour Resin temperature: 245℃ C4 Side Feeder Orifice: Sheet type <Cooling conditions> The sheet-shaped PVA resin was adjusted to a thickness of 2.5 mm and a width of 200 mm using two belt coolers (manufactured by Nippon Belting Co., Ltd.) and cooled. Belt speed: 9m / min Cooling temperature (belt up and down): 35℃ <Crushing conditions> The sheet-shaped PVA resin was coarsely crushed and finely crushed using a hammer crusher and a Makino-type crusher (manufactured by Makino Sangyo Co., Ltd.) to obtain particles of the PVA resin. Hammer crusher Rotation speed: 2500 rpm Screen diameter: φ6 mm Makino type crusher Rotation speed: 5600 rpm Screen diameter: φ3 mm
[0066] <Comparative Example 1> PVA resin particles of Comparative Example 1 were obtained in the same manner as in Example 1, except that the PVA resin was melt-kneaded under the following conditions at a discharge rate of 100 kg / hour, extruded into a strand shape, and then cooled by air. <Melt kneading conditions> Temperature settings: C1 / C2 / C3 / C4 / C5 / C6 / C7 / C8 / C9 / C10 / H1 / D1 / D2 / D3 =50 / 90 / 170 / 180 / 190 / 200 / 210 / 210 / 210 / 210 / 210 / 210 / 210 / 210 / 210℃ Screw rotation speed: 100 rpm Discharge amount: 100kg / hour Resin temperature: 220℃ C4 Side Feeder Orifice: Strand
[0067] <Comparative Example 2> PVA resin particles of Comparative Example 2 were obtained in the same manner as in Comparative Example 1, except that melt kneading was performed under the following conditions at a discharge rate of 250 kg / hour to obtain strands. <Melt kneading conditions> Temperature settings: C1 / C2 / C3 / C4 / C5 / C6 / C7 / C8 / C9 / C10 / H1 / D1 / D2 / D3 =50 / 200 / 200 / 200 / 220 / 230 / 230 / 240 / 240 / 240 / 240 / 240 / 230 / 240℃ Screw rotation speed: 240 rpm Discharge amount: 250kg / hour Resin temperature: 245℃ C4 Side Feeder Orifice: Strand
[0068] The following evaluations were carried out for the above Example 1 and Comparative Examples 1 and 2. The results are shown in Table 1 below.
[0069] [Long-term performance] Regarding the above-mentioned Example 1 and Comparative Examples 1 and 2, when the carbonyl group-containing PVA-based resin was melt-kneaded and extruded under the above-mentioned conditions for 8 consecutive hours, it was visually confirmed whether gel was generated near the discharge part of the extruder, and the results were evaluated according to the following criteria. [Evaluation Criteria] Very good: No gel was generated. ×(poor) Gel occurs
[0070] [Absorbance] The obtained particles of each PVA resin were dissolved in water to prepare a 0.1% aqueous solution, which was used as a sample for absorbance measurement. The absorbance of this sample was measured at a wavelength of 280 nm using a UV-Vis-NIR spectrophotometer (V-560 manufactured by JASCO Corporation). The sample container (cell) used was 1 cm thick.
[0071] [Table 1]
[0072] From the results in Table 1 above, the production method of Example 1 not only had a large discharge amount and high productivity, but also had excellent long-run properties, and the absorbance at 280 nm of the obtained PVA-based resin was 0.2 or more. On the other hand, in the manufacturing method of Comparative Example 1, the melt-kneaded PVA resin was extruded in the form of strands, so the discharge amount was small and the productivity was poor. In addition, the production method of Comparative Example 2 had a large discharge amount and was highly productive, but gel was generated near the discharge part of the extruder, and the production method was poor in long-run properties. Moreover, the PVA resin obtained by the production method of Example 1 is useful as a dispersant for suspension polymerization of vinyl compounds.
[0073] In the above embodiment, specific embodiments of the present invention are shown, but the above embodiment is merely illustrative and should not be interpreted as being limiting. Various modifications that are obvious to those skilled in the art are intended to be within the scope of the present invention. [Industrial Applicability]
[0074] The method for producing a PVA resin of the present invention has high productivity and excellent long-run properties, and the obtained PVA resin is useful as a dispersant for suspension polymerization of vinyl chloride.
Claims
1. A method for producing a polyvinyl alcohol-based resin having an absorbance of 0.2 or more at 280 nm, comprising the steps of melt-kneading a raw material polyvinyl alcohol-based resin and extruding it into a sheet, cooling the sheet-like polyvinyl alcohol-based resin, and pulverizing the cooled sheet-like polyvinyl alcohol-based resin, wherein the step of cooling the sheet-like polyvinyl alcohol-based resin is a step of cooling the sheet-like polyvinyl alcohol-based resin by sandwiching it between a belt cooler.
2. 2. The method for producing a polyvinyl alcohol resin according to claim 1, wherein the raw material polyvinyl alcohol resin is a carbonyl group-containing polyvinyl alcohol resin.
3. 3. The method for producing a polyvinyl alcohol resin according to claim 1, which produces a polyvinyl alcohol resin to be used as a dispersant for suspension polymerization of vinyl compounds.
Citation Information
Patent Citations
Manufacture of water absorption resin composition extrusion molded product
JP1990057305A
Vinyl chloride-based resin composition with electron beam resistance
JP1992261451A
Production of polyarylene sulfide composition
JP1993093023A
Control means for completion of discharge, resin pelletizing apparatus, and manufacturing method for resin pellets using the same
JP2003285321A
Polyvinyl alcohol-based dispersant having conjugated double bond in molecule
JP2004250695A